Towards a Sociology of Reasonableness: Structure and Action in the Structural Interactionist Approach - Tronca, Luigi; Forsé, Michel (Italian Sociological Review, 2022)
The principal aim of this article is to provide an introduction to structural interactionism, in particular examining its relationship to the concepts of structure and action, and the relationship between these two. The structural interactionist approach represents a distinct relational sociology perspective distinguished by its emergentist reading of the relationship between action and social structure. In this article, after presenting an overview of contemporary relational sociologies and examining the fundamental differences between relationist/relationalist sociologies on one side and structuralist sociologies on the other, we will expound the structural interactionist approach, starting with the relationship between structure and action and reserving attention for the concept of reasonableness. Lastly, we will discuss the methodological concerns surrounding structural interactionism, outlining a peculiar relationship in the process of social research between Social Network Analysis and qualitative research techniques.